An analysis of the causes of non-excusable delays by contractor for public projects in Sarawak/ Mohamad Rafiq Mohamad Radzuan - Mohamad Radzuan, Mohamad Rafiq (2020)
Project delay is one of the fundamental constraints to attain the project goals in developing countries and are among the most popular occurrences in the construction sector. The aim of this research is to study the causes of non-excusable delays made by the contractors by analysing from any of the public projects in Sarawak, identifying the causes of non-excusable delays made by the contractors, study on the factors contributing to the causes of the non-excusable delays thus determining the ways to minimise and mitigate the causes of the said delays. lnterviews will be conducted to public projects stakeholders primarily to contract administrators in the public sector in Kuching, Sarawak to obtain a more define results to meet the objectives of this research. Poor management and lack of efficiency in the management of domestic subcontractors are the major reasons why the events of non excusable delays happens in public projects in Sarawak obtained based on the findings done. The factors that lead to these causes are due to the contractor's own poor management skills such as managing their sub-contracts players and arising financial difficulties. The propose way to approach this matter as a way of mitigating and helping to minimize these delay events is by offering a consistent process for the main contractor to assess the subcontractor's tender. Even so, the researcher would like to suggest that the contractor consult regularly with the domestic subcontract players to achieve progress.